Characterization of Rural Organizations in a Forest-Based Economy: A Socio-Institutional Approach - Brahim, Marwa Ben; Nasr, Jamel Ben; Zaibet, Lokman (Asian Journal of Agriculture and Rural Development, 2021)
We used a socio-institutional approach to characterize rural organizations in forest-based communities in North West Tunisia. This approach builds on the imperatives of a social system, the conservation of rural capital, and the role of social capital. The resulting model was used to characterize rural organizations based on key socio-institutional attributes. The paper used a Participatory Rural Appraisal (focus groups mainly) to conduct in-depth analysis in nine forest communities. Results reveal the following : 1) in Development Committees there is a strong belief in state intervention and moderate natural capital appropriation, weak conflict management, weak capacity to sanction, and low trust in the organization; 2) in active Agricultural Development Groups there exists a strong potential for conflict management, trust in the organization, and natural capital appropriation, but a lower level of degradation responsibility and capacity to sanction; and 3) in the Inactive Agricultural Development Groups there is the strongest perception of state intervention and overall weak performances in terms of conflict management, trust in organization, and degradation responsibility. These features indicate the organization’s attributes for sustainable local development and specifically for common forest resources management.